Effect of Infant Prematurity on Auditory Brainstem Response at Preschool Age - Hasani, Sara (Mashhad University of Medical Sciences, 2013)
INTRODUCTION: Preterm birth is a risk factor for a number of conditions that requires comprehensive examination. Our study was designed to investigate the impact of preterm birth on the processing of auditory stimuli and brain structures at the brainstem level at a preschool age. MATERIALS AND METHODS: An auditory brainstem response (ABR) test was performed with low rates of stimuli in 60 children aged 4 to 6 years. Thirty subjects had been born following a very preterm labor or late-preterm labor and 30 control subjects had been born following a full-term labor. RESULTS: Significant differences in the ABR test result were observed in terms of the inter-peak intervals of the I–III and III–V waves, and the absolute latency of the III wave (P<0.019). No significant differences were observed in the amplitude of the I or V waves. The choice of test ear examined had no effect on the results. CONCLUSION: Our results indicate an effect of preterm birth on ABRs and synchronization of auditory stimuli at preschool age, and suggest the need for further follow-up over the coming years.